Multiple Regression Studies on Various Economic Traits of Antheraea mylitta Reared on Seven Forest Tree Species in Uttarakhand, India - Bhatia, Narendra Kumar (Indian Forester, 2021)
In Tropical Tasar pre-cocoon sector, regression studies are executed to examine the kind of existing relationship between or among different variables to find out potential predictor(s) for desired economic traits of A. mylitta. Results indicated that the larval weight gain (g) has significant positive regression weight (Î² = 1.002, t = 346.777, P = <0.05) on mean weight of silk gland. However, emergence percentage of â™€ moth had significant positive regression weight (Î² = 0.209, t = 2.588, P = < 0.05) on mean copulation percentage of A. mylitta that indicates that emergence percentage of â™€ moths is a strong predictor for the mean copulation percentage of A. mylitta. Out of five studied predictors, only mean weight of moths (Î² = 0.491, t = 9.44, P = < 0.05) had significant positive regression weight on mean hatching percentage of A. mylitta that indicates that male moths weight is strong predictors for improved mean hatching percentage of A. mylitta. Post cocoon regression model of the studies indicated that mean silk filament length (Î² = -0.651, t = -12.785, P = < 0.05) had significant negative regression weight and raw silk recovery percentage (Î² = 0.358, t = 9.487, P = < 0.05) had positive regression weight on mean denier of the silk filament of A. mylitta. It shows that with increasing mean silk filament length, its denier is expected to decrease which means, longer the filament, finer it will be.